2019
DOI: 10.1038/s41467-018-07867-7
|View full text |Cite
|
Sign up to set email alerts
|

Trans-ethnic kidney function association study reveals putative causal genes and effects on kidney-specific disease aetiologies

Abstract: Chronic kidney disease (CKD) affects ~10% of the global population, with considerable ethnic differences in prevalence and aetiology. We assemble genome-wide association studies of estimated glomerular filtration rate (eGFR), a measure of kidney function that defines CKD, in 312,468 individuals of diverse ancestry. We identify 127 distinct association signals with homogeneous effects on eGFR across ancestries and enrichment in genomic annotations including kidney-specific histone modifications. Fine-mapping re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 90 publications
(150 reference statements)
9
144
1
1
Order By: Relevance
“…We used lead SNPs from a trans-ethnic meta-analysis [3] of eGFR to evaluate the predictive power of an unweighted GRS into unrelated individuals in the Uganda population ( Table 2).…”
Section: Transferability Of Trans-ethnic Egfr Grs Into Ugandamentioning
confidence: 99%
See 1 more Smart Citation
“…We used lead SNPs from a trans-ethnic meta-analysis [3] of eGFR to evaluate the predictive power of an unweighted GRS into unrelated individuals in the Uganda population ( Table 2).…”
Section: Transferability Of Trans-ethnic Egfr Grs Into Ugandamentioning
confidence: 99%
“…The marked genomic diversity and allelic differentiation among populations in Africa, in combination with the substantially lower linkage disequilibrium (LD) among genetic variants, provides excellent opportunities to gain new insights into disease aetiology and genetic fine-mapping that have relevance for all ancestry groups. However, despite the value of conducting such research in Africa, there is no known genome-wide association study (GWAS) of kidney function in continental Africa, with published studies of African ancestry individuals being limited to African Americans [3,4] . Whilst African Americans typically have a large proportion of African ancestry, several studies have shown that the genetic architecture of African Americans is distinct from that of Africans from continental Africa [5].…”
Section: Introductionmentioning
confidence: 99%
“…We also leveraged summary statistics manually downloaded from recent large association studies for Chronic Kidney Disease 39 , blood lipids 40 , Atrial Fibrillation, Type-II Diabetes, Coronary Artery Disease, estimated glomerular filtration rate 41 , albuminuria 42 , and anthropometric traits 43 . Two proteins, PDL2 and TNFRSF10C, had both cis and trans associations where the trans did not fall in a highly pleiotropic gene.…”
Section: Two-sample Mrmentioning
confidence: 99%
“…Reports on the association between kidney function decline and incident hypertension have been more limited 11 12 . Analysis of the causal effects of lower kidney function on higher blood pressure has inconsistent results 13 . Evaluating the causal relations between kidney function and blood pressure can inform disease prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Haas et al showed evidence supporting the existence of a feed-forward loop between albuminuria, a marker of kidney damage, and hypertension 16 . Morris et al reported significant causal effect of lower kidney function on higher diastolic blood pressure (DBP) and not on systolic blood pressure (SBP) 13 . Two-sample Mendelian randomisation analysis is an extension of the Mendelian randomisation method that allows the use of summary statistics of genome-wide association studies (GWAS) for conducting Mendelian randomisation studies.…”
Section: Introductionmentioning
confidence: 99%